2001
DOI: 10.1046/j.1440-1762.2001.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner–hospital communications: A review of discharge summaries

Abstract: The objective of this study was to examine the reliability, effectiveness, accuracy and timeliness of hospital to general practitioner (GP) information transfer by discharge summaries produced in a general public hospital in New South Wales, Australia. A retrospective audit of 569 patient discharge summaries and related medical records with a targeted GP interview was performed to determine receipt and clinical value of the recorded information. The main outcome measure was the number and quality of discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
121
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 10 publications
8
121
2
5
Order By: Relevance
“…The lowest frequency of PEs reported in the discharge prescriptions were 20%, 17% and 6.3%, 10,[23][24][25] which are lower than our study reported (33.3%). Our study results are different from Callen et al where they reported that electronic discharge summaries have no impact on reducing MEs, according to them handwritten and electronic summaries have a similar rate of PEs which are contrary to our study as we have reported a reduction in incidence of PEs by using the electronic system.…”
Section: Discussioncontrasting
confidence: 86%
“…The lowest frequency of PEs reported in the discharge prescriptions were 20%, 17% and 6.3%, 10,[23][24][25] which are lower than our study reported (33.3%). Our study results are different from Callen et al where they reported that electronic discharge summaries have no impact on reducing MEs, according to them handwritten and electronic summaries have a similar rate of PEs which are contrary to our study as we have reported a reduction in incidence of PEs by using the electronic system.…”
Section: Discussioncontrasting
confidence: 86%
“…However, several authors have found discharge summaries are often missing important information, including discharge diagnosis, pending tests, follow-up plans, and discharge medications. [13][14][15][16] In our study, physicians frequently communicated to clarify similar clinical data, further supporting prior evidence that the discharge summary is frequently inadequate. Our study has several important limitations.…”
Section: Discussionsupporting
confidence: 81%
“…Medication errors are, however, also frequent at the interface between levels of care [31][32][33]. In order to minimise this problem, we have also developed and evaluated separate methods for use at admission to [34] and discharge from [35][36][37] hospital.…”
Section: Discussionmentioning
confidence: 99%